Apoyo para desarrollo de carrera de miembros de “familias de doble carrera” - Jáuregui Machuca, Kety (2010)
Dual-career families, where both spouses seek to develop their own careers, represent thenew social standard. This paper explores the type of support perceived as most relevant to careerdevelopment for a professional member in a dual career family. Quantitative data was compiled us-ing non-probabilistic sampling; the sample consisted of 51 employees belonging to dual-careerfamilies. Results show that organizational support is very relevant to career development, particu-larly in emotional, informational and instrumental dimensions. The second determinant is familysupport, where the emotional dimension was more critical. This study in the Peruvian context coin-cides with the findings of previous studies. Conclusions are that dual-career families perceive or-ganizational support as a priority for their development; therefore, the study proposes that busi-nesses should implement policies related to the emotional, informational and instrumental dimen-sion in their career development plans.